Capital budgeting practice: a survey in Petronas Melaka refinery / Faeiz Hasan Abrar and Hazryati Hamdan (Faculty of Business and Management, 2007)
Today, in line with its strategic vision to become the Best Refinery in Asia Pacific region, PETRONAS Melaka Refinery is embarking on many investment projects such as refinery expansion and new products development. Even though the refinery had many successful projects in the past, there were several big projects that failed due to economic reasons (non-profitable). In retrospect, to select the best investment decisions, a proper capital budgeting process is essential because an inappropriate budgeting decision is a recipe for failure. Academics have highlighted several theories regarding effective capital budgeting process. The issue here is whether PETRONAS Melaka Refinery practices what academics preach when it comes to capital budgeting. Therefore, the objective of this research is to identify the current capital budgeting practice in PETRONAS Melaka Refinery and to investigate the reasons why the practice differs with academics' theory. The data collection method is by questionnaire surveys that were distributed to related employees of PETRONAS Melaka Refinery regarding the current capital budgeting practices. The conclusion of the research is that PETRONAS Melaka Refinery is not entirely following the Capital Budgeting theories that have been advised by academics, such as their preference to use IRR while academics suggested that NPV is a much superior technique that supports the wealth maximization goals of a company. Based on the results of the research, it is proposed that PETRONAS Melaka Refinery to 1) develop Capital Budgeting procedure and ensure its implementation, 2) use NPV as the primary techniques, 3) develop an easy to use evaluation template preferably using spreadsheet program such as Excel for easy NPV and IRR calculation and 4) include Post Audit as a requirement to gauge a project's success.